2017
DOI: 10.1097/cin.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Information-Seeking Behavior of Greek Nursing Students

Abstract: The aim of this study was to investigate factors influencing the use of electronic journals by nursing students through identification of information needs, information resources used, and barriers to seeking information. A cross-sectional study was conducted using a specially designed structured questionnaire. Of 600 nursing students, 505 agreed to participate, indicating a response rate of 84.2%. Participants sought out nurses and doctors, printed materials, scholarly databases/e-journals, and seminars as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, nurses and nursing students experience several barriers and frustrations to seeking and accessing information: a lack of computer skills or, more specifically, database searching skills (Argyri et al, 2014;Dee & Stanley, 2005;Intas et al, 2016); frustration with choosing the right words or phrases to query information resources (Duncan & Holtslander, 2012); lack of access to computers or Internet connections (Raj, Sharma, Singh, & Goel, 2015;Sarbaz, Kimiafar, Sheikhtaheri, Taherzadeh, & Eslami, 2016); and resistance to evidence based practice (Kahouei, Babamohamadi, Panahi, & Zadeh, 2013). Nurses and students need better training using mobile technology, including apps, in clinical, classroom, and laboratory settings (Baro & Ebhomeya, 2013;Majid et al, 2011;Raman, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nurses and nursing students experience several barriers and frustrations to seeking and accessing information: a lack of computer skills or, more specifically, database searching skills (Argyri et al, 2014;Dee & Stanley, 2005;Intas et al, 2016); frustration with choosing the right words or phrases to query information resources (Duncan & Holtslander, 2012); lack of access to computers or Internet connections (Raj, Sharma, Singh, & Goel, 2015;Sarbaz, Kimiafar, Sheikhtaheri, Taherzadeh, & Eslami, 2016); and resistance to evidence based practice (Kahouei, Babamohamadi, Panahi, & Zadeh, 2013). Nurses and students need better training using mobile technology, including apps, in clinical, classroom, and laboratory settings (Baro & Ebhomeya, 2013;Majid et al, 2011;Raman, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers chose the survey as a data collection tool to reach a large number of geographically dispersed respondents with a set of standardized questions. Survey question topics and themes were informed by questionnaire-based research studies on nurses' and nursing students' information behaviour (Argyri, Kostagiolas, Diomidous, 2014;Baro & Ebhomeya, 2013;Intas et al, 2016;Kumaran & Chipanshi, 2015;Majid et al, 2011;O'Leary & Ni Mhaolrúnaigh, 2012;Sarbaz,et al, 2016;Wahoush & Banfield, 2014), specifically those studies which included their survey instruments (Dee & Stanley, 2005;Farrell, Goosney, & Hutchens, 2013;Pravikoff, Tanner, & Pierce, 2005). The survey questions, in a variety of formats including multiple choice and open-ended questions, were pre-tested and revised where necessary to prevent misinterpretation and bias.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…In general, both nursing students and nurses are not always very apt in using new technologies, such as smartphones and health apps, in their clinical practice and they need to increase their ehealth literacy (Andreou 2017; Stergiannis et al 2017). Nursing students in Greece reported as sources of information mainly the nurses and doctors in their clinical placements, printed materials, and to a lesser extend scholarly databases/e‐journals, and seminars (Intas et al 2017). Nevertheless, it has been shown that contextual factors, such as the type of the university they study, in addition to personal self‐efficacy factors, for example, attitudes toward the Internet, self‐rated Internet skills etc., were determinants of ehealth literacy (Rathnayake & Senevirathna 2019; Tubaishat & Habiballah 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Electronic health information literacy competences are likely to improve work practices and the quality of care, together with meeting the needs of patients (Intas et al, 2017; Kostagiolas et al, 2014; Kostagiolas et al 2015). Therefore, it is important to point out these factors that may foster such nurses’ behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For nurses and physicians, the use of these medical databases is a legitimate part of their clinical function [2], improves patient care [3], and facilitates professional development [4] and decision-making for both patients and health care practitioners [5]. Lack of information retrieval skills and training in online search techniques [6] and the required investment in time [4,7,8] and cost [8] constitute major obstacles to searching for clinical information [7,9]. Nurses are required to possess basic knowledge and multiple skills to perform their clinical role: critical and analytical thinking, searching skills, critical reading skills, and critical evaluation of research [10].…”
Section: Introductionmentioning
confidence: 99%